Impact of Delayed Addition of Anti-EGFR Monoclonal Antibodies on the Outcome of First-Line Therapy in Metastatic Colorectal Cancer Patients: a Retrospective Registry-Based Analysis - Fiala, Ondrej; Veskrnova, Veronika; Chloupkova, Renata; Poprach, Alexandr; Kiss, Igor; Kopeckova, Katerina; Dusek, Ladislav; Slavicek, Lubomir; Kohoutek, Milan; Finek, Jindrich; Svoboda, Marek; Petruzelka, Lubos; et al. (Targeted oncology, 2018)
BACKGROUND: The addition of monoclonal antibodies targeting the epidermal growth factor receptor (anti-EGFR Abs) to chemotherapy for metastatic colorectal carcinoma (mCRC) is commonly delayed in the real-world clinical practice, usually because of late RAS testing results. OBJECTIVE: To determine whether delayed addition of anti-EGFR mAbs up to the fourth cycle of backbone chemotherapy adversely affected outcomes of mCRC patients treated with first-line regimens. PATIENTS AND METHODS: Clinical data of patients with histologically verified, RAS wild-type mCRC treated with first-line systemic therapy regimens containing anti-EGFR mAbs were retrospectively analysed from a national database. Patients were divided into three groups according to the timing of anti-EGFR mAbs addition to the chemotherapy backbone. Cohort A (n = 401) included patients in whom anti-EGFR mAbs were added to chemotherapy from the first cycle, cohort B (n = 71) patients with anti-EGFR mAbs added to chemotherapy from the second cycle, and cohort C (n = 101) patients who had anti-EGFR mAbs added to chemotherapy from the third or fourth cycle. RESULTS: Three hundred and thirty-six (58.6%) patients received panitumumab and 237 (41.4%) patients received cetuximab. The median progression-free survival (PFS) of the whole cohort was 12.2 months (95% confidence interval [CI] 10.9-13.5), and the median overall survival (OS) was 33.5 months (95% CI 27.6-39.4). The median PFS and OS for patients treated with anti-EGFR mAbs added to chemotherapy were 12.9 (95% CI 11.5-14.3) and 30.6 months (95% CI 25.2-36.1) for cohort A, 9.7 (95% CI 9.1-10.3) and not reached for cohort B, compared to 11.5 (95% CI 9.8-13.2) and 37.9 months (95% CI 28.6-47.3) for cohort C, respectively. CONCLUSIONS: Delayed addition of anti-EGFR mAbs to first-line chemotherapy was not associated with inferior survival or response rates.
Keywords: Registries; Humans; lidé středního věku; registrace; Antibodies, Monoclonal; Aged; Female; dospělí; senioři; lidé; Adult; Neoplasm Metastasis; metastázy nádorů; ženské pohlaví; kolorektální nádory; Male; Middle Aged; Retrospective Studies; monoklonální protilátky; retrospektivní studie; mužské pohlaví; Colorectal Neoplasms